Membaca Gejala “Mediatisasi” Politik di Indonesia - Noveri Faikar Urfan (Program Studi Ilmu Komunikasi, 2011)
Mediatization is considered as a process oriented of high modernity in which the media become an independent institution with logic of its own that other social institution accommodate to, especially politics. In the past, the media were the subordinate of politics, because the process of communication is centralized by political institution, in particular by political party, so the media were dominated by political logic. But now, after taking a large proliferation, media become omnipresent, so the logic of the media is widespread to any other social institutions. In some degree, politics have to accommodate the media logic. The logic of the media refers to the function of media as the “medium”, and constructing symbolic resource.